Genome-Wide Identification and Analysis of the Cytochrome B5 Protein Family in Chinese Cabbage (Brassica rapa L. ssp. Pekinensis) - Han Zheng; Xin Li; Lin Shi; Ying Jing; Qingqing Song; Yanan Chen; Lilong He; Fengde Wang; Jianwei Gao; Yuping Bi (International Journal of Genomics)
Cytochrome B5 (CB5) family proteins play an important role in various oxidation/reduction reactions in cells as the electron donor and are involved in a variety of biotic and abiotic stress processes. However, the function of the CB5s in Brassica rapa is still unclear. In this study, we carried out genome-wide identification, characterization, and expression analysis of BrCB5s in different tissues under adversities and stresses. It was identified that fifteen BrCB5s were distributed on different chromosomes, which were classified into seven groups (A-G) according to its phylogenetic relationship. Phylogenetic analysis of the CB5 protein sequences from six species showed that the BrCB5s conduct a close evolutionary process with the CB5s of Arabidopsis thaliana and far from those of Oryza sativa. Protein interaction analysis showed that 40 interaction patterns were predicted including two Sucrose Transporter 4 subfamily proteins (SUT 4) and Fatty Acid Hydroxylase 2 protein (FAH 2) can interact with most members of BrCB5s. The expression profile analysis indicated that BrCB5s were differentially expressed in different tissues, and the transcript abundances were significantly different under various abiotic stresses and plant hormone treatments. Our study provides a basis for a better understanding of the characteristics and biological functions of the CB5 family genes in Chinese cabbage during plant development, especially in plant responses to multiple stresses.